Answer:
y = 4,-6
Step-by-step explanation:
0 property states that 0 times any number is 0
applying that here, that means y+6 = 0 or y-4 = 0
0(y-4) = 0; (y+6)(0) = 0
y+ 6 = 0
y = -6
y-4 = 0
y = 4
13 cm+ 13 cm= 26 cm, 26 cm is the answer to Part B.
Answer:
it will take at least 10 weeks of saving to buy the bike
7) (12 + 6)/(2 +4)
(18)/(6) = 3
8) (42 - 24)/6
(18)/6 = 3
9) (9 + 16) - (2 x 4)
25 - 8 = 17
10) 60 - (3 + 2) x 5
60 - 5 x 5
60 - 25 = 35
11) 18 + (9/3)
18 + 3 = 21
12) 5 x (2 + 4 + 3)
5 x (9) = 45
hope this helps